Determining surgical surge capacity with a hybrid simulation exercise - Blimark, Magnus; Robinson, Yohan; Jacobson, Catharina; Lönroth, Hans; Boffard, Kenneth D.; Lennquist Montán, Kristina; Laesser, Ilja; Örtenwall, Per (Frontiers in Public Health, 2023)
BACKGROUND: To help test and improve surgical surge capacity, mass casualty incident (MCI) exercises generate valuable information. Both large scale table-top exercises (TTX) and full-scale exercises (FSX) have limitations if you want to test an organisation's capability and structure. A hybrid exercise incorporating the advantages of TTX and FSX is a possible way forward, but is no standardised exercise method, yet. This study aims at evaluating the exercise results to determine the feasibility of a hybrid TTX/FSX exercise for an organization's capability and structure.METHODS: A hybrid MCI simulation using moulaged figurants and simulation cards was designed, where the emergency department of a level 1 trauma centre receives 103 casualties over 4 hours. After registration and triage, all casualties are expected to be resuscitated in real time and are transferred for further treatment inside the hospital (radiology, operating theatres, intensive care unit (ICU)/postop and wards). When reaching operation theatre, ICU or ward, figurants are replaced by simulation cards. Observers ensured that those procedures performed were adequate and adhered to realistic times. Use of resources (materials, drugs etc) were registered. Primary endpoint was average time spent in the Emergency Department, from time of arrival, to transfer out. Secondary endpoints were related to patient flow and avoidable fatalities.The hospital managed to deal with the flow of patients without collapse of existing systems. Operating theatres as well as ICU and ward beds were available at the end of the exercise. Several details in the hospital response were observed that had not been noticed during previous TTX.CONCLUSION: FSX have a valuable role in training, equipping, exercising, and evaluating MCI management. Hybrid simulations combining both FSX and TTX may optimise resource utilisation and allow more frequent exercises with similar organisational benefit.